Impact of prolonged high altitude exposure on plasma prolactin in men: Effect of age and ethnicity - Sachidhanandam, M.; Singh, S. N.; Ray, U. S.; Salhan, A. K. (High Altitude Medicine & Biology, 2009)
Hormonal changes during high-altitude (HA) exposure are important for normal adaptation to the new environment in lowlanders. Prolactin (PRL), a stress hormone, is involved in the regulation of fertility, immune response, osmotic balance, and angiogenesis. However, little is known about the effect of age and ethnicity on plasma PRL changes in men during prolonged HA exposure. The aim of this research was to examine possible age and ethnic variation in plasma PRL levels in men after 3 to 4 weeks of stay at HA (4500m) in the Indian population. Lowlanders of Rajput (n=49), Gorkha (n=70), and South Indian (n=40) ethnicities were studied at sea level (SL). They were taken to an altitude of 4500m where they stayed for 3 to 4 weeks. Another group of HA natives (Ladakhi, n=65) was studied at similar altitude. Subjects were between 20 to 50yr of age. At HA, plasma PRL showed a decrease in Rajputs and Gorkhas (p<0.05), whereas there was an increase (p<0.05) in South Indians when compared to SL. There was no age variation in PRL. PRL levels in HA natives were within the SL normal range observed in lowlanders. PRL response to HA stress in lowlanders is influenced by ethnicity. The exact cause for such differences in PRL secretion under HA stress is not clearly known. Further studies on the physiological regulation of PRL at HA are needed.